Renegade : defending democracy and liberty in our divided country - Kinzinger, Adam; D'Antonio, Michael, 1955- (The Open Field/Penguin Life, 2023)
"From former Illinois Congressman Adam Kinzinger, a gripping account of the January 6 committee, examining the forces that led to the attacks on the Capitol. On January 6, 2021, America watched in horror as a violent mob led by right-wing extremist groups stormed the U.S. Capitol in support of then-President Donald Trump. It was one of the darkest days in recent history, yet to former Illinois Congressman Adam Kinzinger it was also the culmination of a cultural and political rupture he'd known had long been building. Constructive criticism from within the Republican party was no longer enough. It was time to act-not just for the sake of the soul of his party, but for the very future of our country. Despite vitriol from the media, fellow colleagues, even members of his own family, Kinzinger became one of only two Republican members to join the House select committee to investigate the January 6 Capitol riots. Now in Renegade, he reveals the inner workings and surprising findings of the committee he served and helped lead, including how the bloody attack on the Capitol was indeed foreseeable and even welcomed by President Trump. Along the way, he examines the forces that allowed such an attack to happen in the first place, from the misinformation campaign waged by Fox News and partisan media to the inculcation of extremism in families and faith communities, and draws from his own personal story of faith, military service, and politics to unpack his most crucial decisions that eventually led him to break from his own party. Part memoir, part searing examination, Renegade offers a searing account of one of the most tumultuous events in recent American history-and the devastating consequences of letting extremism go unchecked, so that the events of January 6 may never happen again"--